The Clicking Elateroidea from Chinese Mesozoic Deposits (Insecta, Coleoptera) - Muona, Jyrki (Insects, 2020)
SIMPLE SUMMARY: Fossil click beetles from the family Elateridae are frequent in Mesozoic deposits, especially in Russia and China. In order to understand their relationship to extant species, we need to search for evolutionary important characters that unite these dinosaur-era beetles with extant forms. We show that about one third of the identifiable click-beetles described from Mesozoic Chinese deposits are in fact members of other related families. Our results strengthen the view that these beetle groups are significantly older than often assumed, being present in the Early Jurassic. This is an important result as it indicates that molecular studies based on modern species do not replace paleontology—both are needed, even in the future. ABSTRACT: Recent molecular studies have suggested that the clicking beetle families Elateridae, Eucnemidae, Throscidae, and Cerophytidae evolved in the Jurassic and diversified in the Cretaceous. These studies paid little attention to fossils, using them only as dating tools. The identification of Elateridae fossils is challenging, as external synapomorphies are not known for this family. Elateridae can be identified only as something not belonging to the other related families, all of which have diagnostic synapomorphies. Most subfamilies and tribes of Elateridae do possess definite diagnostic characters, however, making their identification feasible. We checked the 28 Elateridae described from Chinese Mesozoic deposits. Twelve were Elateridae, seven were Eucnemidae, and one was a Throscidae. Three species could be Eucnemidae, but showed aberrant characters. Five species could not be placed and may not belong to Elateroidea at all. On the basis of these results we suggest that all previously described Elateridae fossils should be re-checked. They should be searched for synapomorphies defining Eucnemidae, Throscidae, and Cerophytidae. If such characters are not present, a click beetle type of fossil can be placed in Elateroidae incertae sedis. The Mesozoic Chinese Elateridae fossils all belong to clades that do not exist today, whereas the Mesozoic Eucnemidae subfamilies are extant ones. This may be the source of the disagreement between Elateridae fossil age and datings based on molecular studies. One new combination was made: Desmatus ponomarenkoi (Chang, Kiretjshuk & Ren, 2009) NEW COMBINATION (= Paradesmatus ponomarenkoi Chang, Kirejtshuk & Ren, 2009).